2016
DOI: 10.1186/s40337-016-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Adult picky eaters with symptoms of avoidant/restrictive food intake disorder: comparable distress and comorbidity but different eating behaviors compared to those with disordered eating symptoms

Abstract: Background: One presentation of Avoidant/Restrictive Food Intake Disorder (ARFID) is characterized by picky eating, i.e., selective eating based on the sensory properties of food. The present study has two aims. The first is to describe distress and impairment in individuals with ARFID secondary to picky eating. The second is to determine whether eating behaviors hypothesized to be specific to picky eating can differentiate picky eaters with and without ARFID from typical eaters (e.g., individuals not reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 40 publications
2
64
0
5
Order By: Relevance
“…Thus, in our study, both groups reported food avoidance, but those with ARFID reported even more difficulty trying new foods than those with AN, representing the only scale endorsed more strongly by those with ARFID than those with AN. This pattern replicates findings from an online community sample in which adults with normative eating behaviors reported lower scores on the FNS than those with eating disorder attitudes but adults with both selective eating and ARFID symptoms showed the highest scores on the FNS (Zickgraf et al, ). Notably, we found no differences between the groups in endorsement of dietary restriction on the EPSI Restriction subscale.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Thus, in our study, both groups reported food avoidance, but those with ARFID reported even more difficulty trying new foods than those with AN, representing the only scale endorsed more strongly by those with ARFID than those with AN. This pattern replicates findings from an online community sample in which adults with normative eating behaviors reported lower scores on the FNS than those with eating disorder attitudes but adults with both selective eating and ARFID symptoms showed the highest scores on the FNS (Zickgraf et al, ). Notably, we found no differences between the groups in endorsement of dietary restriction on the EPSI Restriction subscale.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, in this sample a subset of patients were referred for an eating disorder evaluation by other medical providers because of irregular eating habits and associated risks and/or medical sequelae and others were self‐referred due to distress associated with their symptoms. Using a modified version of the CIA that excludes thoughts about weight, shape, eating, and exercise (Wildes, Zucker, & Marcus, ), adults from an online community sample, who identified as picky eaters and endorsed ARFID symptoms, reported equivalent levels of impairment from eating behaviors as adults who endorsed traditional eating pathology (i.e., concern about weight, shape, and eating; Zickgraf et al, ). Given these findings and knowledge of our sample, we cannot conclude that individuals with ARFID have lower levels of life impairment associated with their eating behaviors than individuals with AN or lack insight into their symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations